The Civil Religion Debate: Is Pancasila a Substitute for or a Protector of Traditional Faiths? - Andri Fransiskus Gultom; Genoveva Mari (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2025)
The conceptualization of Pancasila as Indonesia’s state ideology often oscillates between being a political umbrella and a potential civil religion. This debate has intensified as global populism and religious conservatism challenge the traditional boundaries of national identity. This study aims to philosophically and sociologically investigate whether Pancasila functions as a substitute for traditional faiths or strictly as a protector of religious pluralism (a neutral arbiter). Employing a qualitative approach with a phenomenological-hermeneutic design, this research was conducted between January to December 2024 across three strategic loci: Jakarta, Yogyakarta, and Manado. Data were gathered through in-depth interviews with 15 key informants. The findings reveal a Third Way paradigm: Pancasila does not substitute the transcendental essence of traditional religions but acts as a Sacred Civic Framework. The novelty of this research lies in the discovery of Civic-Religious Synchronicity, where Pancasila facilitates the sacralization of civic duties without secularizing the faith itself, effectively preventing the totalitarianism of belief often found in theocracies. This study implies that strengthening Pancasila as a Protector rather than a Substitute is vital for democratic resilience.